Enfoque terapéutico de la pericoronaritis asociada a terceros molares inferiores. - Ocaña Campoverde, Carlos Daniel (2025)
The present research study aimed to analyze the therapeutic approach for managing pericoronitis associated with lower third molars. To this end, a systematic review was conducted according to the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) methodological guidelines to ensure accurate study selection. The PICO strategy was also established to formulate the research questions. The studies were collected from various scientific databases such as Google Scholar, Scopus, PubMed, and Cochrane. A population of 23 eligible studies was included for analysis, which were selected according to the inclusion criteria. The results of this research report that the degree of angulation of the third molars is a crucial factor in developing this anomaly. According to the Pell & Gregory classification, the prevalent position is class IIA, while the mesioangular position is the most significant according to the Winter classification. Furthermore, the reviewed research reveals that several authors propose a range of therapeutic methods, both conventional and surgical, aimed at improving patients' clinical presentation and quality of life. In conclusion, there is currently no ideal consensus on treating pericoronitis, thus underscoring the importance of promoting additional studies to ensure more effective and optimized comprehensive care.